Differentiating Latent Tuberculosis from Active Tuberculosis Through Activation Phenotypes and Chemokine Markers HLA-DR, CD38, MCP-1, and RANTES: A Systematic Review and Meta-Analysis - Chaimae Kadi; Narjisse Ahmadi; Anass Houdou; Imad El Badisy; Oumnia Bouaddi; Zakaria Mennane; Nouhaila Najimi; Maryam Benlamari; Saber Boutayeb; Mohamed Khalis; Noureddine EL Mtili; Fouad Seghrouchni (Biomarker Insights)
Background: Latent TB infection (LTBI) affects one fourth of the global population. Currently, there is an absence of an optimal strategy for distinguishing between active tuberculosis (aTB) and LTBI. While some researchers have explored cytokines other than interferon-gamma (IFN-γ) as biomarkers, results have shown significant variability in their ability to differentiate between these conditions. This meta-analysis aims to evaluate the performance of activation phenotype and chemokine markers in distinguishing between aTB and LTBI. Objectives: To assess the diagnostic accuracy of specific biomarkers (HLA-DR + IFNγ + , CD38 + IFNγ + , MCP-1, and RANTES) in differentiating aTB from LTBI. Design: This study was conducted in accordance with the PRISMA guidelines for systematic reviews and meta-analyses of diagnostic studies. Data sources and methods: We conducted a comprehensive search of PubMed, Scopus, Sciences Direct, and Web of Science for primary studies published in English up to 2023. Studies were included if they reported sensitivity, specificity, diagnostic odds ratio (DOR), and area under the curve (AUC) for the biomarkers in question. We calculated pooled diagnostic sensitivity, specificity, DOR, and AUC, and used the summary receiver operating characteristic curve (SROC) to summarize the diagnostic performance of each biomarker. Results: Sixteen studies involving 1696 participants were included in the analysis. Among them, 925 individuals were diagnosed with aTB, while 771 were classified as having LTBI. The specificity, sensitivity, DOR, and AUC for CD38 + IFNγ + , HLA-DR + IFNγ + , RANTES, and MCP-1 were (0.97 [95% CI: 0.72-1.00], 0.90 [95% CI: 0.75-0.96], 291.863, and 0.9432), (0.90 [95% CI: 0.70-0.97], 0.83 [95% CI: 0.63-0.94], 41.819, and 0.8598), (0.68 [95% CI: 0.55-0.79], 0.72 [95% CI: 0.56-0.84], 5.733, and 0.7979), and (0.63 [95% CI: 0.54-0.72], 0.63 [95% CI: 0.50-0.75], 2.892, and 0.7290) respectively. Conclusion: The findings indicate that CD38 + IFNγ + and HLA-DR + IFNγ + demonstrated the highest diagnostic accuracy. Additional prospective research is necessary to identify the optimal combination of biomarkers to enhance diagnostic accuracy in clinical settings. Registration: This review has been registered on PROSPERO: (CRD42023472091). Available from: https://www.crd.york.ac.uk/prospero/#recordDetails